WT1: The Hinge Between Anemia Correction and Cancer Development in Chronic Kidney Disease - Lee, Wen-Chin; Chiu, Chien-Hua; Chu, Tian-Huei; Chien, Yu-Shu (Frontiers in Cell and Developmental Biology, 2022)
Hypoxia-inducible factor-prolyl hydroxylase inhibitors (HIF-PHIs) emerge as promising agents to treat anemia in chronic kidney disease (CKD) but the major concern is their correlated risk of cancer development and progression. The Wilms’ tumor gene, WT1, is transcriptionally regulated by HIF and is known to play a crucial role in tumorigenesis and invasiveness of certain types of cancers. From the mechanism of action of HIF–PHIs, to cancer hypoxia and the biological significance of WT1, this review will discuss the link between HIF, WT1, anemia correction, and cancer. We aimed to reveal the research gaps and offer a focused strategy to monitor the development and progression of specific types of cancer when using HIF–PHIs to treat anemia in CKD patients. In addition, to facilitate the long-term use of HIF–PHIs in anemic CKD patients, we will discuss the strategy of WT1 inhibition to reduce the development and progression of cancer.